Benefits of Implementing Earned Value Management in Construction Projects in Nigeria - Albert, Idowu; Bilau, Abdulquadri Ade; Osadola, Opeyemi Ayodeji; Baiyegunhi, Clara Morenike (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study examines the principles, benefits, and readiness for Earned Value Management (EVM) within the Nigerian construction industry. It focuses on how EVM can address persistent performance challenges, including cost overruns, schedule delays, and weak monitoring and reporting practices. A quantitative research design was employed, with data collected from 151 construction professionals in Ogun State using a stratified sampling technique. Respondents consisted of architects, engineers, builders, and quantity surveyors. Data were analysed using SPSS to evaluate awareness levels and perceptions of key EVM concepts and performance indicators. The results indicate high awareness of fundamental EVM components such as Planned Value, Earned Value, Actual Cost, and related performance indices among construction professionals. Respondents strongly agreed that EVM enhances cost and schedule control, promotes proactive decision-making, and supports accountability and transparent performance monitoring. Additional benefits identified include improved communication, reduced disputes, and better post-project learning. Despite these strengths, actual adoption remains limited due to inadequate digital systems, insufficient technical capacity, and organisational constraints. The study highlights the need for targeted capacity development, integration of EVM into organisational project management procedures, investment in digital performance-tracking systems, and clearer policy frameworks to enable effective implementation. Strengthening these areas can significantly improve project delivery outcomes in Nigeria. This research provides empirical evidence on EVM awareness, perceived benefits, and adoption challenges within a developing construction context. It offers practical insights that can guide industry stakeholders, policymakers, and organisations seeking to enhance project performance through structured control systems such as EVM.